The Experiences of Students with Disabilities Actually Doing Service Learning: A Systematic Review. (March 2023) - Garwood, Justin D.; Peltier, Corey; Ciullo, Stephen; Wissinger, Daniel; McKenna, John W.; Giangreco, Michael F.; Kervick, Colby
Background: There are many examples of school-based interventions involving a service learning project aimed at helping students with disabilities, but it is potentially more impactful on the students with disabilities for them to be active participants in service learning, rather than merely its recipients.Purpose: The purpose of this article is to present a synthesis and analysis of all available research studies focused on service learning where the students with disabilities were active participants in the service learning, rather than passive recipients of interventions.Methodology/Approach: We assessed all available studies ( N  = 13), including eight peer-reviewed journal articles and five dissertations, for content and for research quality according to established design standards for quantitative ( n  = 3), qualitative ( n  = 6), and mixed methods ( n  = 4) research.Findings/Conclusions: Favorable evidence in support of service learning participation for students with disabilities exists in the available qualitative and mixed methods research, but evidence from quantitative research is lacking.Implications: The activity-based, often motivating opportunities to learn and apply a wide range of academic and functional life skills are abundant in service learning. We urge practitioners to consider implementing this practice, while also noting the need for more empirical research.